Developing regional voluntary carbon markets for peatlands: innovation processes and influencing factors. (7th February 2023) - Chen, Cheng; Loft, Lasse; Sattler, Claudia; Matzdorf, Bettina
ABSTRACT: Integrating peatland restoration measures with climate policy is critical for meeting climate targets, but the current policies often fall short of utilizing the large potential that exists. Despite growing private sector interest, few regional voluntary carbon markets for peatlands have emerged worldwide. In this study, we explore three pioneering examples from Europe. From the perspective of social innovation, we aim to provide clarity on how these innovations emerged and developed, which actors drove the innovation process by assuming which roles, and which factors fostered or hindered the development. We do so by mapping the innovation process using Process Net-Map. The results show that all three cases have followed remarkably similar patterns in their innovation processes. Four phases, i.e. preparation, definition, refinement, and up-scaling were identified, as were actors' roles as innovators, promoters, intermediaries, implementers, and knowledge providers. However, the case studies are very different with regard to which actor constellation drove the innovation process: MoorFutures is driven by public and scientific actors, Valuta vor Veen is promoted by civil society actors in consultation with practitioners, and Hiilipörssi shifted from civil society to private actors. The governance modes, that is, actor constellation and their goals, have led to differences in concept, robustness of methodology, mitigation measure, and possibly potential for up-scaling. Our study indicates that the timing of interventions when actors with certain roles stepped in can accelerate the innovation process. Important political, economic, technical, and social factors influencing the innovation process, especially knowledge and trust accumulated between some key actors, are outlined. Key policy insights: Private funding for regional voluntary carbon markets (VCMs) can tap the climate mitigation potential from peatlands, which is not currently adequately addressed by governments. Actor constellation drove the innovation process, leading to different concepts, methodologies, and mitigation measures. The timing of interventions by actors, notably providing seed funding, network, expertise and visibility, was critical for success. Building trust for regional VCMs requires not only a robust methodology to calculate emission reductions but also partnership and endorsement. The future development of climate policy on peatlands could be a decisive factor in regional VCMs.